2022-RA-1094-ESGO Implementation of a tri-modal prehabilitation intervention – KORE-INNOVATION: the first prospective clinical trial to assess a perioperative pathway to reduce postoperative complications in ovarian cancer patients. (20th October 2022) - Inci-Turan, Melisa Guelhan; Lee, Marlene; Rattunde, Magdalena; Schneider, Stephanie; Schnura, Eva; Klews, Julia; Bergjan, Manuela; Algharably, Engi; Sehouli, Adak Pirmorady; Reißhauer, Anett; Knappe-Drzikova, Barbora; Zwanzleitner, Lena; et al.
Abstract : Introduction/Background: The effectiveness of prehabilitation in improving physical capacity for patients undergoing surgery has been shown for patients in orthopedic, abdominal, or cardiological surgeries. Ovarian cancer patients have an exceptionally high risk for severe postoperative complications due to the extent of the surgical treatment, often including multi-visceral resection. We report our first experiences of implementing a tri-modal prehabilitation intervention as part of the KORE-INNOVATION trial. Methodology: KORE-INNOVATION is an ongoing clinical trial to implement and assess an innovative perioperative care pathway to reduce complications (primary endpoint) for patients undergoing surgery for ovarian cancer through the implementation of a prehabilitation strategy combined with the 'enhanced recovery after surgery' (ERAS)-pathway. The prehabilitation intervention consists of three modules: a personalized empowerment intervention, a personalized physical exercise-program-, and a personalized metabolic screening and nutrition intervention. Before prehabilitation, a complex baseline assessment, consisting of the Fried frailty assessment, metabolic and physical assessments, and detailed patient history, is performed to develop a personalized prehabilitation plan targeting individual deficits ( figure 1 ). Results: Prehabilitation ranged from one to three weeks and was overseen by a multi professional and interdisciplinary KORE team of physicians, nurses, physiotherapists, and nutritionists. The majority of patients conducted prehabilitation as outpatients. Weekly phone calls were made to monitor patients' adherence and adjust treatment plans, if necessary. Patients reported feeling more capacitated and resilient after undergoing the prehabilitation program. Conclusion: A structured, individualized prehabilitation program delivered through a specialized multi professional team presents an opportunity to prepare patients holistically for the stressful experience of debulking surgery and might contribute to faster postoperative reconditioning. Prehabilitation is an important addition to the ERAS pathway and should be considered a relevant part of perioperative care.